Revisiting Targeting in Social Assistance : A New Look at Old Dilemmas - Grosh, Margaret; Leite, Phillippe; Wai-Poi, Matthew; Tesliuc, Emil (Washington, DC: World Bank, 2022)
Targeting is a commonly used, but much debated, policy within global social assistance practice. This book examines the well- known dilemmas in light of the growing body of experience, new implementation capacities, and the potential to bring new data and data science to bear.